Cell-to-Cell Spread of Wild-Type Herpes Simplex Virus Type 1, but Not of Syncytial Strains, Is Mediated by the Immunoglobulin-Like Receptors That Mediate Virion Entry, Nectin1 (PRR1/HveC/HIgR) and Nectin2 (PRR2/HveB) - Cocchi, Francesca (American Society for Microbiology, 2000)
The immunoglobulin-like receptors that mediate entry of herpes simplex virus type 1 (HSV-1) into human cells were found to mediate the direct cell-to-cell spread of wild-type virus. The receptors here designated Nectin1α and -δ and Nectin2α were originally designated HIgR, PRR1/HveC, and PRR2α/HveB, respectively. We report the following. (i) Wild-type HSV-1 spreads from cell to cell in J cells expressing nectin1α or nectin1δ but not in parental J cells that are devoid of entry receptors. A monoclonal antibody to nectin1, which blocks entry, also blocked cell-to-cell spread in nectin1-expressing J cells. Moreover, wild-type virus did not spread from a receptor-positive to a receptor-negative cell. (ii) The antibody to nectin1 blocked transmission of wild-type virus in a number of human cell lines, with varying efficiencies, suggesting that nectin1 is the principal mediator of wild-type virus spread in a variety of human cell lines. (iii) Nectin1 did not mediate cell fusion induced by the syncytial strains HSV-1(MP) and HFEM-syn. (iv) Nectin2α could serve as a receptor for spread of a mutant virus carrying the L25P substitution in glycoprotein D, but not of wild-type virus, in agreement with its ability to mediate entry of the mutant but not of wild-type virus.